The perception on mobile-based interactive learning media use in archiving course completion - Patni Ninghardjanti; Chairul Huda Atma Dirgatama (Institute of Advanced Engineering and Science, 2022)
This research analyzed the discriminant of different categories of successfully passing and remedial students based on the perception on mobile-based interactive archiving media. The research method employed quantitative approach with questionnaire instrument. The questionnaire was distributed to students attending Archiving class using interactive archiving media having been developed by the author previously. Data analysis involved prerequisite test analysis including validity and reliability tests. Data was then analyzed using discriminant analysis model with SPSS version 23 application software. The result of research showed that: i) There is a significant difference of perception on interactive media between successfully passing and remedial students; ii) Media originality variable is the one determining the significance of difference; and iii) Discrimination model has high accuracy, so that this research can be used for further research and development with similar theme and variable.